Postoperative Pain Management Following Craniosynostosis Repair: Current Practices and Future Directions. Issue 3 (May 2019) - Brown, Stav; Yao, Amy; Sanati-Mehrizy, Paymon; Zackai, Sheemon P.; Taub, Peter J.
Abstract : Background: Postoperative analgesia following craniosynostosis repair is a clinical challenge for plastic and reconstructive surgeons. There is a paucity of published data on the postoperative pain associated with craniosynostosis repair procedures and the prescribed analgesia varies with different unit protocols. The authors sought to summarize the current knowledge of the postoperative analgesia following craniosynostosis repair by reviewing the literature for existing regimens, clinical outcomes, and recommendations. Methods: Two independent investigators conducted a literature search of the Pubmed, Cochrane, and Google Scholar databases for relevant clinical studies. Studies were abstracted for procedure type, postoperative pain management protocol, pain scores, side effects, complications, and clinical recommendations. Results: Ten studies describing the use of analgesic agents in open craniosynostosis surgery from 2000 to 2018 were fully reviewed, comprising a total of 431 patients undergoing surgical procedures using a combination regimen of narcotic and nonnarcotic agents (n = 315) and nonnarcotic agents alone (n = 116). Conclusion: Multimodal analgesia is the primary regimen used following open craniosynostosis repair procedures. Opioids are a critical component in pain management regimens, relieving patient discomfort. However, due to the deleterious effects that come with their prolonged use, intravenous acetaminophen is currently used as an alternative in many centers. The preferred mode of pain medication administration in the pediatric population is increasingly via the intravenous route which ensures that a full dose of pain medication is given. The authors suggest the use of dexmedetomidine, both an adjunct to intravenous acetaminophen and as a substitute for morphine due to its superior safety and efficacy profile.